Step 1) Let a , b , c , d be non-zero numbers that exist in the complex set of numbers. Let these numbers also satisfy the equation a + b = c d
Step 2) We can divide both sides by c : a + b = c d ⟹ c a + b = d
Step 3) We can subtract d from both sides: c a + b = d ⟹ c a + b − d = 0
Step 4) We can divide both sides by c a + b − d : c a + b − d = 0 ⟹ c a + b − d c a + b − d = c a + b − d 0 Since any number divided by itself is equal to 1 and 0 divided by any number is equal to 0 , we can conclude that 1 = 0 : c a + b − d c a + b − d = c a + b − d 0 ⟹ 1 = 0 □
Of course this proof is 1 0 0 % valid, but try to find any flaws. If you find one, what step is it?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Technically, c a + b − d c a + b − d = 0 0 = 0 so the proof is valid but it only proves that 0 = 0 .
Log in to reply
Read this on zero divided by zero . Since it is undefined, it doesn't have a specific answer; it could be 1, it could be 0, it could be ∞ . Because of this, it cannot be used in proofs since it is such a controversial topic
Log in to reply
@James Watson that is something of controversy, I do not think we can include that here till it is clarified.
Log in to reply
@Shevy Doc – that is why it makes the proof invalid
Reading the "!" as a factorial, the option "Of course 1 = 0!" is a true statement :-)
Log in to reply
indeed, but "it is all valid" isn't lol
Aaaaaaaaaaaaaaaaalmost lol :v
If only you didn't add the "it is all valid" :v
It’s invalid on step 3. Step 4 is wrong, but step 3 comes first. A = 7 B = 5 C = 4 D = 3 7 + 5 = 12. 12/4 = 3. 2 is good 12/4-3=0 is 0=0. 3 is bad, technically true, but not 1=0 0/0=0/0 is true technically the only x/0 possible, so 4 is okay. Note: I said okay, not good 5 is okay since 3 creates the wrong. Still not good, but okay.
Log in to reply
division by 0 with any number including 0 is not possible. the correct term is it is indeterminate. for step 3, ending up with a 0=0 situation is valid and doesn't break any mathematical axioms so it wouldn't cause any issues. it is only after we "divide by 0" that we end up with our flawed statement of 1 = 0
In step three we found c a + b − d = 0 , in step 4 we went on to divide by that. Although there are two options 'correct' here (I mean 1= 0!).
what is the second option?
Log in to reply
1=0! is a true statement
Log in to reply
oh yeah haha!
Log in to reply
@James Watson – It was a great thing to put there
Log in to reply
@A Former Brilliant Member – it wasn't on purpose xd
Log in to reply
@James Watson – Now that's more interesting
Totally wrong!
Log in to reply
Where's the error, if the whole is wrong why's that?
I disagree. As Devbrat stated, c a + b − d = 0 and division by 0 is not allowed which is what happened on step 4 so the explanation is valid
You've proved that the expression in step 4 evaluates to 0. Hence, you cannot use that expression as a denominator since such an evaluation is undefined.
Of course 1=0!
The 4th step is wrong, because we can't divide by 0.
Problem Loading...
Note Loading...
Set Loading...
The flaw is in step 4 . Given that c a + b − d = 0 , we cannot divide by it because division by 0 is impossible, so the proof loses any validity.